Genetic and environmental variation and genotype x environment interactions in New Zealand Romney sheep : [microform] a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University - Newman, Sheryl-Anne Ngaire (Massey University, 1988)
Performance records were kept on New Zealand Romney ewes from birth to 5 years of age. These ewes were maintained in two subflocks at different stocking rates. A proportion of the ewes were eliminated at random at about 16 months of age. From this stage until 5 years all ewes were retained unless they died of natural causes. The data represented 1944 hoggets and 919 older ewes, the progeny of 49 sires. Each of these sires were used for two consecutive years. The records were calculated between 1966 and 1983 and represented seven sire periods. The significance of genotype x environment interactions (GEI) were investigated for a range of hogget and adult traits, including liveweight (LW), greasy fleece weight (GFW), clean fleece weight (CFW), yield (Y) , quality number (QN), mean fibre diameter (MFD) , staple length (SL) , total crimp number (TCN) , crimp frequency (CF) , staple strength (SST), character (CHG), lustre (LUS), tippiness (TIP), cotting (COT), cotted area (CAG), soundness (SOU), handle (HND), greasy midside colour (GCM), secured midside colour (SCM), greasy fleece colour (GCF), number of lambs born per ewe mated (NLB), number of lambs weaned per ewe mated (NLW), weight of lamb weaned (WLW), weight per lamb weaned (WPL) and lamb survival percentage (LSP). The effects of the environmental factors of birth year, age, number of lambs born and weaned, stocking rate and rearing rank and all interactions among them were assessed for ewe liveweight and wool traits. A similar model was developed for hogget traits but included age at weaning rather than reproductive status. Reproductive trait models included ewe liveweight and did not include rearing rank and reproductive status. Sire x stocking rate and sire x birth year interactions were the only genotype x environment interactions that were should occur at the 'commercial' stocking rate. The environment of the stud should be taken into account when selecting rams. Significant GEI will also have important implications in relation to breeding systems used to assist genetic improvement of the sheep population. Group breeding schemes and sire reference programs will be affected. If the GBS nucleus is in a different environment from the base flocks, both closed and open schemes can suffer a considerable loss in overall selection response when GEI exist. Comparison of sires across flocks using sire referencing is currently receiving much attention. If sire x environment interactions are important, inconsistencies are likely to occur in the ranking of sires. Genotype x year interactions appear likely to be a major cause of inconsistencies in the estimation of breeding values and research to identify the causes of these interactions should be carried out.
Keywords: Romney sheep; Sheep genetics